Features of the Application of the Amnesty Institution under the Laws of the Russian Empire (1845-1917) - G. G. Dedurin; D. G. Zavrichko (Bulletin of Kharkiv National University of Internal Affairs)
The peculiarities of the application of the amnesty institution under the legislation of the Russian Empire are studied, in particular, the Regulations on Criminal and Correctional Punishments of 1845, 1885, 1903, tsarist manifestos, the Amnesty Act of 1905, etc. Thus, the normative consolidation of concepts and partially the procedures of “pardon” and “condonation” was reflected in the Criminal and Correctional Penal Code of 1845, which were duplicated in the Regulations of 1885 and 1903. The reasons for the abolition of punishment could be the following: incurable illness or death of the accused, reconciliation of the parties, the statute of limitations for the crime and pardon. According to the norms of the Code, pardon of criminals came from the supreme autocratic power and the sovereign’s mercy.